Ultrasonic assisted machining - Ascroft, Helen; Barnes, Stuart; Dahnel, Aishah Najiah; Gupta, Aniruddha; Abd Halim, Nor Farah Huda; Ray, David (Middle East Technical University, 2016)
A commercially available DMG MORI ULTRASONIC 65 monoBLOCK machining centre was installed in WMG in 2013 and has been primarily used to machine aerospace grade materials such as carbon fibre reinforced plastic (CFRP) and titanium alloy Ti 6Al-4V (individually and stacked) and 2000 / 6000 series aluminium alloys. Rather than discuss a single set of experimental work in detail, this paper discusses some of the issues that have been encountered when applying the technique of ultrasonic assisted machining (UAM) and some of the effects that have been observed using examples from the research conducted so far to illustrate some of the more important findings.